APPLICATION OF HYPERBOLIC FUNCTIONS FOR ANALYSIS OF TAKEN DECISIONS IN ECOLOGICAL MANAGEMENT - S. A. Laptionok; S. V. Dorozhko; V. P. Bubnov; N. V. Arsiutkin (Наука и техника)
A methodology for application of hyperbolic functions with the purpose to make estimation of the taken decisions in ecological management is presented in the paper. The paper provides examples of an analysis concerning the possibility to realize forecast targets in accordance with the given terms.